Enhanced aromatics selectivity and stability in a coaromatization reaction over P/[ZnCr]/HZSM-5. Issue 5 (25th January 2023) - Lv, Junmin; Wang, Dan; Zhu, Bing; Li, Haibo; Fan, Subing; Zhao, Tian-sheng
Abstract : P/[ZnCr]/HZSM-5 showed a higher BTEX yield of 87.5 wt% and higher stability due to less coke in the coaromatization of methanol coupling with n -hexane. Abstract : A coaromatization reaction is an effective process for heat-coupling and safety. A comparison study of [ZnCr]/HZSM-5 with P/[ZnCr]/HZSM-5 in the coaromatization of methanol and n -hexane was performed. The relative properties of catalysts were analyzed by means of XRD, FT-IR, py-FTIR, ICP, N2 sorption, TG, Raman, and so on. [ZnCr]/HZSM-5 showed high selectivity to BTEX but lower stability at high temperature. Meanwhile, P modification tuned the acidity and texture, resulting in a higher BTEX yield of 87.5 wt% and more stability. Moreover, the product distribution was further changed to gaseous C1 –C3 hydrocarbons and liquid aromatics, which is beneficial to the separation. In addition, the deactivation reasons were also explored. The deactivation reason for [ZnCr]/HZSM-5 is ascribed to both the loss of framework AlF and the carbon deposit, while for P/[ZnCr]/HZSM-5 it is mainly the carbon deposit.